IMPLEMENTASI SUPERVISI PENDIDIKAN SEBAGAI SARANA PENINGKATAN KINERJA GURU DALAM KEGIATAN BELAJAR MENGAJAR - Opi Rohmawati; Poniyah Poniyah; Adiyono Adiyono (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Educational supervision is a planned coaching activity to assist teachers and other school employees in carrying out their work effectively. The teacher is the main role holder in an education because the teacher determines the success of students, especially in the process of teaching and learning activities. Therefore, educational supervision is carried out as a means to provide opportunities for teachers to develop and carry out their main tasks, by improving and increasing teacher performance in the teaching and learning process. This research method uses a library study method (library research), namely a method of collecting data by understanding and studying theories from various literature related to the research (Adlini, et al, 2022). This research uses a qualitative approach because this research activity is descriptive in nature by collecting information and data such as the results of previous similar studies, as well as various journals.